Are Mast Cells MASTers in Cancer? - Varricchi, Gilda; Galdiero, Maria Rosaria; Loffredo, Stefania; Marone, Giancarlo; Iannone, Raffaella; Marone, Gianni; Granata, Francescopaolo (Frontiers in Immunology, 2017)
Prolonged low grade inflammation or smoldering inflammation is a hallmark of cancer. Mast cells form a heterogeneous population of immune cells with differences in their ultra-structure, morphology, mediator content and surface receptors. Mast cells are widely distributed throughout all tissues and are stromal components of the inflammatory microenvironment that modulates tumor initiation and development. Although canonically associated with allergic disorders, mast cells are a major source of protumorigenic (e.g., angiogenic and lymphangiogenic factors) and anti-tumorigenic molecules (e.g., TNF- and IL-9) depending on the milieu. In certain neoplasias (e.g., gastric, thyroid, and Hodgkin’s lymphoma) mast cells play a protumorigenic role, in others (e.g., breast cancer) a protective role, whereas in yet others they are apparently innocent bystanders. These seemingly conflicting results suggest that the role of mast cells and their mediators could be cancer-specific. The microlocalization (e.g., peritumoral vs intratumoral) of mast cells is another important aspect in the initiation/progression of solid and hematologic tumors. Increasing evidence in certain experimental models indicate that targeting mast cells and/or their mediators represent a potential therapeutic target in cancer. Thus, mast cells deserve focused consideration also as therapeutic targets in different types of tumors. There are many unanswered questions that should be addressed before we understand whether mast cells are an ally, adversary or innocent bystanders in human cancers.